ANALISIS PENYEBAB PENINGKATAN DURASI REPARASI MT. RATU RUWAIDAH DENGAN FTA DAN FMECA - Betty Nur Kumala; Fitri Hardiyanti; Devina Puspita Sari (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2024)
According to Dock News data on repair projects throughout 2022 carried out at PT PAL Indonesia's Dock shows that the MT Ratu Ruwaidah repair project is the only project that has increased duration, which is 64 days. The purpose of the research is to find out the root cause of the increase in duration, evaluate the risks, and find out the recommendations for handling. Starting with the Fault Tree Analysis method to obtain the Minimal Cut Set of the root cause of the increase. Furthermore, determining the Minimal Cut Set as a failure mode for Severity, Occurrence and Detection assessment by respondents to be processed in the Failure Modes, Effect and Criticality Analysis method. With the risk treatment matrix, failure modes can be identified how to handle them. The result of the research is that there are 23 events from the minimum cut set that are determined as failure modes. In the processing of the Failure Modes, Effect And Criticality Analysis method, the Pareto diagram stage obtained only 13 priority event/failure mode codes. As a result, the 13 failure modes occupy the colors red (prevent and mitigate), orange (mitigate) and yellow (prevent) in the risk treatment matrix.